A study on the implementation of KOHA cataloguing module in Malaysian academic libraries - Sarif Abdullah, Sharifah Nur Amirah; Md Nor, Nor Saadah; Nor Yazid, Nurul Aini (UM, 2023)
The study explores the experiences of the Malaysian academic libraries’ cataloguers in their use of the cataloguing module of Koha Open Source Software (OSS). The purpose of this study is to shed light on issues concerning Koha cataloguing module and the local practices in policy and procedure while utilising the module. An exploratory sequential research design was adopted for the study involving an online focus group interview and a questionnaire survey as the data collection techniques. Twenty-two academic libraries from public and private universities in Malaysia were purposively sampled. A total of six academic libraries participated in the focus group, whereas 41 participants took part in the survey. The study highlighted academic libraries in Malaysia embrace Koha for two main reasons - popularity as and OSS and budget constraints for a proprietary library system. The findings of the study revealed that missing records is a significant issue that cataloguers will have to deal with and there is a lack of certain features available in the Koha cataloging module, such as the label creator and search feature. Apart from that, using Koha for cataloguing does not affect the cataloguing practices in terms of policy, but it does affect the cataloguing procedure. Satisfaction level with Koha cataloguing module is high. Other academic libraries in Malaysia that have not yet made a move to Koha or are in the midst of doing so would benefit from this study.